EFL Students’ Perceptions of the Repeated Reading Strategy in Enhancing Reading Fluency - Moh. Alfi Syahrin; Moon Hidayati Otoluwa; Fahria Malabar (Transbahasa, 2025)
This study investigates EFL students’ perceptions of the repeated reading strategy as a method for enhancing reading fluency. Conducted within the English Language Education Study Program at Universitas Negeri Gorontalo during the 2024/2025 academic year, this research adopts a descriptive quantitative approach. A total of 60 first-year students participated in the study through an online Likert-scale questionnaire comprising 30 items categorized into knowledge, perception (absorption, understanding, evaluation), and fluency (accuracy, speed, prosody) indicators. The findings reveal that students exhibit a predominantly positive to very positive perception of the repeated reading strategy. The highest mean scores were observed in prosody (86.33), followed by understanding (82.00), evaluation (82.34), and reading speed (81.89). Although accuracy scored slightly lower (74.44), it still fell within the positive range. These results affirm that students not only understand the purpose and benefits of repeated reading but also experience improvements in expression, comprehension, and confidence when reading aloud. This study supports the integration of repeated reading as an effective and well-perceived pedagogical tool in EFL contexts. It further emphasizes the need to consider students’ perceptions as an essential component in evaluating instructional strategies for reading fluency development.